Survei Kepuasan Kerja Pelanggan Internal (Pegawai) di RSUD K.R.M.T Wongsonegoro Kota Semarang - Widya Ratna Wulan; Faik Agiwahyuanto; Evina Widianawati; Baju Widjasena (Jurnal Kesehatan, 2020)
Hospital as the health care provider institutions need to keep the employee performance as a service quality’s major factor that given to customers. K.R.M.T Wongsonegoro Regional Public Hospital that gave the public health services had done to measure the internal customer (employee) satisfaction through internal customer (employee) survey since 2018. This study aims to analyze the employee’s expectation and satisfaction suitability to the factors that affect work satisfaction as a service quality development in K.R.M.T Wongsonegoro Regional Public Hospital Semarang. This study used survey method. Also used descriptive study design by quantitative-qualitative approach and cross sectional time. Dependent variable is internal customer (employee) satisfaction, while leadership, compensation, work environment, a promotion chance, and supervise as independent variabels. The index average of internal customer (employee) satisfaction as much as 73,8% with satisfaction details related to control of  leadership 75%, compensation (75%), work environment (73%), a promotion chance (74%), and supervision (74%). This item can be concluded that internal customers (employee) in K.R.M.T Wongsonegoro Regional Public Hospital Semarang 2019 is quite satisfied with the institution services seen from leadership and compensation items provided that motivated their  satisfaction, but compensation and the promotion chance need to be improved.